Load sharing in single-lap bonded/bolted composite joints. Part I: Model development and validation. (1st October 2015) - Bodjona, Kobyé; Raju, Karthik; Lim, Gyu-Hyeong; Lessard, Larry
Abstract: The combination of a bonded joint and bolted joint can potentially result in a joint that is stronger and more durable than either constituent separately. Experimental studies have demonstrated that the greatest "across-the-board" improvements (compared to both constituent joints) are obtained when there is substantial load sharing between the adhesive and bolt. However, in practice few bonded/bolted joint designs experience load sharing, with the adhesive transferring most of the load. This work consequently deals with the problem of achieving substantial load sharing in bonded/bolted joints. The joint type studied was a single-bolt, single-lap composite joint containing an elastic–plastic adhesive. The research aim was to identify the most significant design parameters contributing to load sharing and to quantify/rank their importance. To accomplish this, a global sensitivity analysis was conducted of a suitable computational model. In part I of this two-part paper, this model is described and is validated both experimentally and against a high fidelity three-dimensional finite element model. The model predictions are shown to correspond well with both the experiment and high fidelity model, while reducing the computational cost by >95% compared to the latter. The validated model is subsequently used in the sensitivity analysis presented in part II.